PERAN HUMAN CAPITAL BAGI KEUNGGULAN KOMPETITIF ORGANISASI: SEBUAH TINJAUAN - Suryono Efendi (Jurnal Kelola: Jurnal Ilmu Sosial, 2019)
With rising globalization and labor market saturation, the present downturn in many international economies has emphasized the importance of human capital. Both developed and developing countries place a premium on human resource development in order to boost economic growth through increased time and effort. Human resource development is a critical component in entering the international arena. To do this, businesses must invest the required resources in developing human capital that has a stronger influence on performance. From a variety of critical viewpoints, the influence of this paper evaluation on human capital has a direct effect on company performance. The success of the business is measured in both financial and non-financial parameters. Finally, this article develops an early model of the connection between human capital and business performance.